(untitled) (Mongolian Journal of Astronomy and Geophysics, 2024)
Assessing the sensitivity of Mongolia’s seismic stations and determining the minimum threshold for earthquake detection provide essential information for researchers. To evaluate the detection capacity of these stations, each station calculates its self-noise level using the 90th percentile value of the probability density function (PDF) of the power spectral density (PSD), based on data acquired between January 2018 and May 2021. To simulate earthquake detection in Mongolia, we implemented a grid where each point represents an earthquake epicenter. These points are spaced at 10 km intervals. The detection of a seismic wave is determined based on an amplitude attenuated by distance, which must be at least three times higher than the self-noise level of the station. For a point to be considered detectable, at least four stations must register the seismic wave under these conditions. Using these criteria, a detection capability map is generated to assess the overall detection capacity of the network. From the resulting analysis, it can be concluded that the seismic network in Mongolia is capable of detecting earthquakes with a magnitude of 1.8 across the country. In the western and central regions, where station density and sensitivity are higher, the network can detect seismic events as small as magnitude 1.4.